(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
Selenium is an essential element in human nutrition, closely related to human health. Selenium plays an important role in the prevention of various diseases, such as high cholesterol, cardiovascular diseases, and certain types of cancer. Although food and vegetables can be the main source of selenium intake, selenium supplementation is still more in demand in low selenium regions. Selenium deficiency diseases are well known and that large amounts of selenium cause toxicity in humans. Therefore, there must be a simple, rapid, sensitive and economical way to prepare selenium micro-portfolios as dietary supplements. Selenium micro-preservatives were prepared using different polymers such as sodium alginate, chitosan, starch, and casein, by ionic gelation method after adding them to 2% calcium chloride solution. The percentage of reservation when using sodium alginate was 51.2%, 86.37% for chitosan, 23.29% for starch, and 60.87% for casein.